تحليل بق ايا المبيدات الحشرية في بعض المحاصيل الز راعية باستخدام التقنية الكهروكيميائية - بكاري, نور الهدى; قابوسه, جمعه (Université of eloued جامعة الوادي, 2025)
تهدف هذه الدراسة إلى تقييم بقايا المبيدات الحشرية والفطرية في محصول الطماطم المزروع في منطقة المقرن بولاية الوادي، باستخدام تقنيات التحليل الكهروكيميائي، وبشكل خاص تقنية الفولتمترية الدورية (Cyclic Voltammetry) تم التركيز على المادة الفعالة Hymexazol نظراً لتكرار استخدامها كمبيد في المنطقة المدروسة . أُجريت تحاليل دورية لعينات الطماطم على مدى عدة فترات زمنية بعد الرش )من اليوم الثاني حتى ما بعد فترة الأمان(، وقد مكّنت تقنية CV من الكشف عن ثلاث قمم أكسدة مميزة لمركب Hymexazol عند جهود 0.8 ، 1.15 ، و 1.78 فولت، ما يؤكد حساسية التقنية وفعاليتها في تتبع تحلل المبيد في النبات . أظهرت النتائج انخفاضًا تدريجيًا في شدة التيار المرتبط بالمادة الفعالة مع مرور الوقت، إلى أن بلغ مستويات غير قابلة للكشف بعد اليوم العشرين، وهو ما يتوافق مع معايير فترة الأمان الموصى بها. لم تُظهر باقي المبيدات المدروسة CHLORANTRANILIPROLE ، CYPERMETHRIN ، ABAMECTIN ، PIRIMICARB أية قمم كهروكيميائية ضمن مجال الجهد المستخدم، مما يشير إلى عدم تراكم بقاياها في الثمار أو اختلاف آلية امتصاصها . تُبرز هذه الدراسة جدوى وفعالية الطرق الكهروكيميائية كبديل اقتصادي وبيئي لتحليل بقايا المبيدات في المنتجات الزراعية، كما تسلط الضوء على ضرورة المراقبة المنتظمة للممارسات الزراعية، وتعزيز الوعي باستخدام المبيدات ضمن المعايير المسموح بها . This study aims to evaluate the residues of insecticides and fungicides in tomato crops cultivated in the El-Meggarine region of El Oued province, using electrochemical analysis techniques, particularly Cyclic Voltammetry (CV). The focus was placed on the active compound Hymexazol due to its frequent use as a fungicide in the studied area. Tomato samples were analyzed periodically over several time intervals following pesticide application (from the second day up to the post-withdrawal period). CV technique successfully detected three distinct oxidation peaks for Hymexazol at potentials of 0.8, 1.15, and 1.78 V, demonstrating the technique’s sensitivity and effectiveness in tracking pesticide degradation within the plant. Results showed a gradual decrease in the electrochemical current associated with the active substance over time, reaching undetectable levels after 20 days—consistent with the recommended pre-harvest interval. Other studied pesticides (CHLORANTRANILIPROLE ،CYPERMETHRIN ،ABAMECTIN ، PIRIMICARB) did not exhibit any detectable peaks within the tested potential range, suggesting either a lack of residue accumulation or different absorption behavior. This study highlights the feasibility and efficiency of electrochemical methods as cost-effective and environmentally friendly alternatives for pesticide residue analysis in agricultural products. It also emphasizes the need for continuous monitoring of agricultural practices and raising awareness about safe pesticide use within regulatory limits.
Analysis Of Pesticide Residues In Crops Using Electrochemical Technique.
ماستر كيمياء تحليلية
Keywords: : بقايا المبيدات، الفولتمترية الدورية، Hymexazol ، الطماطم، التحليل; Pesticide residues; cyclic voltammetry; Hymexazol; tomatoes; electrochemical analysis